Concept study and preliminary design of a cold atom interferometer for space gravity gradiometry. (10th October 2019) - Trimeche, A; Battelier, B; Becker, D; Bertoldi, A; Bouyer, P; Braxmaier, C; Charron, E; Corgier, R; Cornelius, M; Douch, K; Gaaloul, N; Herrmann, S; et al.
Abstract: We study a space-based gravity gradiometer based on cold atom interferometry and its potential for the Earth's gravitational field mapping. The instrument architecture has been proposed in Carraz et al (2014 Microgravity Sci. Technol . 26 139) and enables high-sensitivity measurements of gravity gradients by using atom interferometers in a differential accelerometer configuration. We present the design of the instrument including its subsystems and analyze the mission scenario, for which we derive the expected instrument performances, the requirements on the sensor and its key subsystems, and the expected impact on the recovery of the Earth gravity field.